Synthesis and Thermoelectric Characterization of Lead Telluride Hollow Nanofibers - Zhang, Miluo; Park, Su-Dong; Kim, Jiwon; Nalbandian, Michael; Kim, Seil; Choa, Yongho; Lim, Jaehong; Myung, Nosang V. (Frontiers in Chemistry, 2018)
Lead telluride (PbTe) nanofibers were fabricated by galvanic displacement of electrospun cobalt nanofibers where their composition and morphology were altered by adjusting the electrolyte composition and diameter of sacrificial cobalt nanofibers. By employing Co instead of Ni as the sacrificial material, residue-free PbTe nanofibers were synthesized. The Pb content of the PbTe nanofibers was slightly affected by the Pb2+ concentration in the electrolyte, while the average outer diameter increased with Pb2+ concentration. The surface morphology of PbTe nanofibers was strongly dependent on the diameter of sacrificial nanofibers where it altered from smooth to rough surface as the Pb2+ concentration increased. Some of thermoelectric properties [i.e., thermopower (S) and electrical conductivity(σ)] were systematically measured as a function of temperature. Energy barrier height (Eb) was found to be one of the key factors affecting the thermoelectric properties–that is, higher energy barrier heights increased the Seebeck coefficient, but lowered the electrical conductivity.